Japan to Pilnyak's poetic: from essay to cycle (on the problem of evolution of Pilnyak's poetic) - I V Zdereva (RUDN Journal of Studies in Literature and Journalism, 2010)
Article is devoted to a problem of art evolution of Pilnyak's poetics considered on an example of the «Japanese» cycle of works. Movement of author's idea from the short forms of narrative to more complicated genre formation is traced in details. Author gives reasons of presence of the major principles of cyclization.